Virtual universities: factors of success and prospects of development - Grinshkun, V.V.; Krasnova, G.A. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Informatizat͡s︡ii͡a︡ obrazovanii͡a, 2018)
This article is devoted to the peculiarities of the formation and functioning of virtual universities, emerging in recent years in different countries of the world. The main approaches to their creation and financing are described. It is noted that along with public virtual universities, private universities are developing, including corporate virtual universities. The main models of virtual universities are classified, including the consortium model, the traditional model of the university with electronic education for individual educational programs, the model of educational organizations of distance learning and the actual virtual university model. Successful models of functioning of virtual universities in Great Britain, USA, Italy, South Korea, Russia and other countries are described. In the widespread model of the consortium, educational organizations jointly develop online courses, provide access to the repository of courses for students of these universities, and also have the opportunity to transfer courses to students of organizations that are members of the consortium. The main factors influencing the development of virtual universities are singled out. Along with successful examples of the implementation of the model of a consortium of educational organizations, negative examples of the functioning of such associations of higher education institutions are presented in the article. In conclusion, the main directions of the development of virtual universities are determined.